Enhanced security for next generation of vehicular network - Ng, Kian Wei (2017)
Today, in-vehicle innovation has brought us to a newer level of the incorporated system being explored and further developed to gain the access of controlling vehicles in our modern life. The typical approach would be utilizing the access of control to the various types of systems in a vehicle implementing the electronic control units (ECUs). These ECUs can be used to interconnect between various vehicle systems which provide convenience of the implementation to application software. Controller Area Network (CAN) bus was designed to enforce the essential needs of the reliability, safety and the real time capability in the network. Despite the absence of the encryption which exploit the vulnerability to the man-in-the-middle attacks eavesdropping or interception of data packets. Nonetheless, precautionary measures is to be taken to prevent the leak of the data transmission and to enforce the security for the CAN bus protocol.